STEM TERMINATION GENETICS IN PIGEONPEA VARIANTS (CAJANUS CAJAN (L.) MILLSP) - D. R. SAPKAL; A. N. PATIL; V. R. SAPKAL; M. P. MESHRAM (The Bioscan, 2015)
In pigeonpea, there are three distinct growth habits of plants types which differ in the morphology of the inflorescence, that are determinate (DT), semideterminte (SDT) and indeterminate (IDT). Growth habit is useful trait because of short stature of the determinate plant types makes them amenable to efficient crop management practices, such as foliar insecticide application and mechanized crop production. Indeterminate plants, on the other hand, grow taller; hence, efficient management and mechanization become difficult. But indeterminate genotypes yielded more than determinate genotype in semiarid environment. Indeterminate plants produce flowers throughout the growing season whenever sufficient moisture is available. This is not possible in case of determinate genotypes. While semideterminate growth habit was rarely observed in pigeonpea germplasm. Inheritance studies of growth habit, indeterminate Vs determinate and indeterminate Vs semideterminate growth habit was studied with seven populations (parents, F 1 , reciprocal, F 2 and both back cross) of eight and two crosses with respective characters. Data analysis of segregating populations (F 2 s and test crosses) was carried out with the help of chi-square test. Present studies showed that indeterminate growth habit was completely dominant over determinate plant type and indeterminate trait was governed by single gene as all F 2 and their test cross progenies segregated and well fitted for 3:1 and 1:1 ratio in cross IDT Vs DT. Inheritance study of indeterminate Vs semideterminate growth habit showed dominant epistatic ratio for two loci of 12:3:1, IDT/ SDT/DT in F 2 population. This result confirmed with test cross and back cross with dominant parents. From present study of IDT Vs SDT, it was concluded that indeterminate growth habit was governed by Dt 1 /dt 2 s and semideterminate as dt 1 / Dt 2s . The presence of Dt 1 allele completely masked the expression of Dt 2 s allele. The presences of the recessive allele of these genes in homozygous state (dt 1 dt 1 , dt 2 s dt 2 s) result in determinate growth habits. While no reciprocal differences were observed in inheritance pattern of IDT Vs DT and IDT Vs SDT, indicating no maternal effect to govern the traits.